DEVELOPMENT OF PROBLEM BASED LEARNING MODULE ON BUFFER SOLUTION AT ELEVEN GRADE ON PUBLIC HIGH SCHOOL IN PONTIANAK - Yuningsih, Siti; Melati, Husna Amalya; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : The research aims to produce problem based learning module on buffer solution of eleven grade that is appropriate as teaching materials. The method used is a Research and Development recommended by Borg & Gall. The sample in this research was determined by disproportionate stratified random sampling and purposive sampling technique. Based on the results of data analysis on the questionnaire obtained: (1) evaluation of the expert judgment in terms of the feasibility of content, feasibility of presentation, feasibility of linguistic and feasibility of graph are respectively 89,74% (very high), 89,27% (very high), 92,5% (very high), and 85,23% (very high); (2) The readability test on initial field trials teacher response is 68,75% (high) and students response is 78,43% (high); and (3) The readability test on major field trials teacher response is 82,49% (very high) and students response is 85,14% (very high). It can be concluded that the module developed feasible used as teaching materials and has a high readability based on the responses of teachers and students. Â  Keywords: Â problem based learning modules, buffer solution